Ammonia Determination In Bottled Water Using Spectrophotometer : Comparison Between Nessler And Berthelot Methods - Sasongko, Ashadi (Universitas Pendidikan Ganesha, 2018)
Ammonium concentration in bottled drinking water should not exceed 0.15 ppm. National Standardization Agency of Indonesia (BSN) had issued two standard methods for analysis, Nessler (SNI 01-03554-1998) and Berthelot (SNI 01-03554-2006). Both were statistically compared. The first method was much simpler than the second one because the preparation was only by adding the Nessler reagent into the sample. Whereas in the second one, the addition of reagents should be prepared freshly. The variance coefficient of the first method was 3.41% with linearity 0.9995 and recovery was 101.05%. Whereas variance coefficient of second method was 3.64 % with linearity 0.9995 and recovery was 105.62%. Significance test between the methods showed that value of Fexp (1.043) was less than Fcrit (4.284),Â and value of texp (2.36) was less than tcritÂ (2.45) in interval of confidence 95%. There was no significant difference between two methods